Generalized -Euler Numbers and Polynomials Associated with -Adic -Integral on - H. Y. Lee; N. S. Jung; J. Y. Kang; C. S. Ryoo (International Journal of Mathematics and Mathematical Sciences)
We generalize the Euler numbers and polynomials by the generalized -Euler numbers and polynomials . We observe an interesting phenomenon of “scattering” of the zeros of the generalized -Euler polynomials in complex plane.